THE MODERATOR ROLE OF ORGANİZATİONAL LEARNİNG İN THE RELATİONSHİP BETWEEN AGİLE LEADERSHİP AND ORGANİZATİONAL AGİLİTY (Third Sector Social Economic Review, 2023)
Organizations that want to achieve their strategic goals in today's economic life, where competition is intense, need agile leadership and an agile organizational structure. Organizations that are open to innovations and have an organizational learning culture will ensure that activities are carried out in a shorter time, with better quality and at less cost. In this study, the relationship between agile leadership and organizational agility and whether organizational learning has a moderator role or not has been investigated. In addition, it was examined whether demographic characteristics differ in agile leadership, organizational agility and organizational learning. The research universe consisted of 470 people working in the private sector in Istanbul. The obtained data were analyzed with SPSS 21.0, and Pearson correlation test and regression analyzes were performed for the moderator role. According to the analysis results, it has been determined that organizational learning has a moderator role in the effect of agile leadership on organizational agility. In addition, it has been found that the variables of agile leadership, organizational agility and organizational learning show some changes according to demographic characteristics such as gender, total work experience, sector, working style, and the number of employees in the workplace. In conclusion, the necessity and importance of agile development to achieve success in leadership are emphasized, and suggestions for business life are presented to increase organizational agility and organizational learning.
Keywords: Agile Leadership; Organizational Agility; Organizational Learning; Organizational Behaviour; Agility